Comparative modeling of socio-economic burden among smokers, nonsmokers and former smokers - E. V. Radchenko; A. S. Kolbin (Фармакоэкономика)
Aim: to assess the socio-economic burden of smoking in the Russian Federation for 2017.Materials and methods. The socio-economic burden was calculated and extrapolated to the entire population of smokers in Russia and then compared with equal sized populations of quitters and non-smokers.Results. In 2017, the burden of tobacco smoking (including the direct costs of medical care and payment for temporary disability, as well as indirect costs - the under-received gross domestic product (GDP) due to temporary disability) was 510.6 billion rubles. The difference between the smokers and the equal-sized non-smoking population is 327.6 billion rubles. The difference between the smokers and the equalsized population of quitters was 216.1 billion rubles.Conclusion. Costs associated with smoking are sizable. Helping quit tobacco smoking (government anti-smoking measures, pharmacotherapy etc.) will not only improve the quality of life and health expectancy of smokers but also save a considerable amount of budget funds.